The answer is 60.50 DO THE MATH LAZY!!!!!!!
Answer:
54
Step-by-step explanation:
x-1=3
2xy=24
3+24=27
27·2=54
Answer:
(1, 4)
Step-by-step explanation:
y=x+3
y=3x+1
y=x+3
x+3=3x+1
x=3x-2
-2x=-2
x=1
y=1+3
y=4
Answer:
x = 4 or x = -1
Step-by-step explanation:
2x^2 - 8x + 6 =0
divide by 2 we get : x^2 -4x +3 = 0
(x -4) (x+1)
x = 4 or x = -1
Answer:
1 and 2
Step-by-step explanation:
If y was 1: -2 x 1 + 18 = -2 + 18
= 16 This works
If y was 2: -2 x 2 + 18 = -4 + 18
= 14 This works
If y was 3: -2 x 3 + 18 = -6 + 18
= 12 This does not work since -2y + 18 has to be <u>greater</u> than 12.